Screening for peripheral artery disease: focus on toe-brachial index - Krisztina Fendrik; Luca Mányi; Florentin Baki; Katalin Koltai; Dóra Endrei; Kálmán Tóth; Gábor Késmárky (Cardiologia Hungarica)
Toe-brachial index (TBI) measurement helps to detect peripheral artery disease (PAD) in patients with incompressible ankle arteries due to medial sclerosis, most frequently associated with diabetes. We want to raise awareness of the toe blood pressure and toe-brachial index. Therefore, we tested an automated four-limb blood pressure monitor that can also measure TBI, and compared the results with conventional ankle-brachial index measurements and other toe blood pressure measuring devices. In 117 patients (mean age 63.2±12.8 years) ankle-brachial index (ABI) measurement was performed with the Doppler-method and the MESI mTablet. TBI was obtained by photoplethysmography (MESI mTablet, SysToe) and a laser Doppler fluxmeter (PeriFlux 5000). Lower limb PAD lesions were evaluated by vascular imaging. A significant correlation was found between Doppler and MESI ankle-brachial index (r=0.672), stronger in non-diabetic (r=0.744) than in diabetic (r=0.562) patients. At an ABI cut-off of 0.9, Doppler (AUC=0.888) showed a sensitivity/specificity of 67.1%/97.4%, MESI 57.0%/100%, at a cut-off of 1.0 MESI 74.7%/94.8%. TBI values measured by the three methods did not differ significantly (p=0.33). At a TBI cut-off of 0.7, MESI (AUC=0.909) revealed a sensitivity/specificity of 92.1%/67.5%. Combining MESI ABI and TBI measurements recognised 92.4% of PAD limbs. Using an ABI cut-off level of 1.0 and the sequential TBI measurement increases the sensitivity of the device in detecting PAD.